PENGEMBANGAN MODUL PEMBELAJARAN BIOLOGI BERBASIS ANDROID PADA MATERI SISTEM REGULASI UNTUK SISWA SMA/MA - Pratama, Halmi; Eliwatis, Eliwatis; Fajar, Najmiatul (Sainstek : Jurnal Sains dan Teknologi, 2018)
Technology that is developing at this paper are believed can help teachers to create learning media. For example, is the use of technology in m-learning's virtual learning media which can be applied to android smartphones. Learning that is currently happening is only conventional and the use of instructional media by teachers has not developed according to technological progress and the use of these technologies has not been applied in learning. Therefore, research is carried out which aims to produce an android-based biology learning module about the material of the regulatory system for SMA / MA students who are valid and practice. This research development using three of the four stages of the development model of 4-D Models, which consist of defining phases, design phases, develop phases, distribution phases (disseminate). The data of this study are primary data obtained from the validation sheet and practicality test questionnaire, then analyzed by descriptive analysis. This research produces a product in the form of a valid and practical biology-based learning module. Based on the validator's assessment, the android-based biology learning module is categorized as very valid (82.84). Based on the assessment of android-based biology subject teachers in the very practical category, the average results of 87.92 were obtained and based on the assessment of students the biology learning module was categorized as very practical and obtained an average value of 86.6. The Android-based biology learning module that the researchers developed is feasible to use in the learning process.